PENINGKATAN PRODUKTIVITAS LAHAN KERING MELALUI PENANAMAN TUMPANGSARI KACANG TANAH DENGAN JAGUNG DI SUBAK BLAHKIUH - Kusumawati, Ni Putu Ayu; Ayu, Putu Cita; Mahayasa, I Gede Aryana; Yuliantari, Ni Putu Yeni (JURNAL SEWAKA BHAKTI, 2025)
Blahkiuh Village is one of the villages in Badung Regency that has Natural Resources (SDA) and Human Resources (SDM) that can potentially be developed. This can be seen from the carrying capacity and availability of land for peanut cultivation. Apart from that, the majority of people earn their living as farmers. Commodities cultivated by the people in Subak Blahkiuh include corn, chilies, water spinach, water henna, long beans and peanuts. Peanuts are one of the secondary crops that have economic value. Peanuts are usually planted in rice fields or moors singly or in pairs in the tumpeng sari system. Peanut plants (Arachis Hypogea L.) are plants that are widely cultivated in Indonesia because the soil conditions and temperature are very suitable and are one type of nut that is widely consumed by Indonesian people. Apart from being a source of protein, carbohydrates and vitamins, it is also used as a cooking spice, boiled peanuts and fried peanuts. This potential can encourage people to be more active in increasing peanut production and productivity. Community empowerment through peanut cultivation is one effort to improve business skills in terms of innovation, promotion, processing and marketing aspects. The method for implementing peanut cultivation activities in Subak Blahkiuh was carried out using qualitative research, using observation methods, interview methods, and training or practical methods. Where this activity is carried out with farmers in cultivating land, planting, pest control and post-harvest.